Late Closure of a Stage III Idiopathic Macular Hole after Pars Plana Vitrectomy - Filiz Afrashi; Zafer Öztaş; Serhad Nalçacı (Türk Oftalmoloji Dergisi, 2015)
A 57-year-old female presented to our hospital with decreased vision in her right eye. Detailed ocular examination was performed, and a macular hole was detected in the right eye. The presence of a full-thickness stage III macular hole was confirmed with optical coherence tomography (OCT) imaging. Pars plana vitrectomy followed by long-acting gas tamponade (C3F8) was performed as treatment. One month after surgery, clinical examination revealed a persistent macular hole, confirmed by an OCT scan. Although the patient was scheduled for reoperation, the surgery was postponed due to personal reasons of the patient. Surprisingly, after five months, a closure pattern with accompanying epiretinal membrane was observed in the macular hole area. The closure of the macular hole was completed without any further intervention 8 months post-surgery. In cases of unclosed macular hole after the first surgery, if a second surgery cannot be performed, follow-up with OCT recommended due to the possibility of spontaneous closure. However, spontaneous closure of a persistent macular hole following PPV is rare, so early diagnosis and surgical repair of unclosed macular holes must remain the primary goal.